Implementasi Konsep Community Based Correction (CBC) dalam Sistem Pemasyarakatan di Lapas Terbuka - Subroto, Mitro; Setiawan, Muhammad Dhea (Universitas Pahlawan Tuanku Tambusai, 2025)
Corrections play a crucial role in the criminal justice system, particularly in the treatment of detainees, juveniles, and inmates. The primary objective of this system is to rehabilitate, develop, and prepare inmates to reintegrate into society as productive members. This research adopts a qualitative and empirical juridical approach to analyze the implementation of the Community-Based Correction (CBC) concept in Open Prisons in Indonesia. The CBC system emphasizes inmate rehabilitation through minimal supervision, community involvement, and various skill development programs. This program aims to reduce recidivism and facilitate social reintegration. The research findings reveal that Open Prisons play a significant role in rehabilitation by offering skill training and activities that support inmates’ independence. However, the success of this program faces challenges such as limited infrastructure, a shortage of supervising officers, and weak institutional support. Nevertheless, collaboration between correctional institutions, the community, and related agencies can enhance the effectiveness of this system. The study concludes that strengthening the CBC system is essential for supporting inmate rehabilitation, reducing recidivism, and promoting better social reintegration.